Legal Protection for Capital Market Investors If the obligation to pay interest and principal on bonds is not fulfilled - Arifardhani, Yoyo; Selian, Stella Sadeva (Faculty of Law, Universitas Pekalongan, 2024)
The Indonesian capital market is growing rapidly and plays a role in national development. Important principles include managing value-added activities, system development, and placing reliable personnel to create Good Corporate Governance (GCG). According to Law no. 8 of 1995, the capital market includes public offerings, securities trading and securities-related public companies. The capital market trades capital and debt instruments. Bonds are long-term debt securities with the risk of the company's inability to fulfill its obligations. This research reviews legal protection for capital market investors in handling bond payment obligations. The aim of this research is to determine the role of legal protection from the Capital Market Regulator in imposing sanctions on public companies that are negligent in fulfilling their obligation to pay interest and/or principal on bonds, and to find out how to ensure investors are safe in purchasing bonds. The research results show that capital market regulators such as the Trustee, OJK, and BEI have a crucial role in supervising and protecting bond holders from pre-registration to post-issuance. Actions include trusteeship contracts, sanctions, and suspension of bond issuers. And in-depth knowledge of bonds and the factors that influence their security will help investors in choosing bonds that suit the investor's risk profile and investment objectives.